Gambaran Pemeriksaan Kadar SGOT, SGPT, Ureum dan Kreatinin Pasien Covid-19 dengan dan tanpa Komorbid - Rachmi Fadillah; Ellyza Nasrul; Tuty Prihandani (Fakultas Kedokteran, Universitas Andalas, 2021)
Coronavirus disease (COVID-19) causes damage through mechanisms: cytotoxic to the bile duct, liver and renal tubular epithelial cells; severe inflammatory response due to excessive pro-inflammatory cytokines (cytokine storm); tissue anoxia; and drug-induced liver and kidney damage. AST and ALT enzymes are used to determine liver damage, while kidney damage is examined from increased urea and creatinine levels. Objectives: To know AST, ALT, urea and creatinine levels in COVID-19 patients with and without comorbidity in RSUP Dr. M. Djamil Padang. Methods: A retrospective descriptive study was conducted by taking chemical data for COVID-19 patients with and without comorbidity for March-August 2020. AST and ALT levels were examined by using an automatic chemistry analyzer with NADH method (without P-5'-P), urea with enzymatic colorimetry, and creatinine with Jaffe's modification. The data was presented in table and average (standard deviation). Results: A study of 76 patients found 28 with comorbidity and 48 without comorbidity. Patients with comorbidity AST in average was 33.0 (20.3) U/l; SGPT 29.0 (23.4) U/l; urea 58.3 (66.9) mg/dl; and creatinine 3.0 (5.1) mg/dl. Patients without comorbidity AST in average 31.9 (28.7) mg/dl; SGPT 28.8 (21.4) mg/dl; urea 24.6 (20.1) mg/dl; creatinine 0.9 (0.4) mg/dl. In average, AST and ALT in patients with and without comorbidity were in the normal range. Urea and creatinine in patients with comorbidity were higher than normal. Conclusion: Covid-19 patients with comorbidity at admission had urea and creatinine levels in average higher than normal values.Keywords: aminotransaminase, COVID-19, creatinine